2010
DOI: 10.4028/www.scientific.net/msf.654-656.1162
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of Electrodeposited Ni-SiO<sub>2</sub> Nanocomposite

Abstract: Nanocomposite materials consisting of a nanocrystalline Ni matrix with grain size ranging from 23 to 40 nm, and nano-size SiO2 particles with average particle size of 7 nm, have been produced by pulse electrodeposition. Grain size was controlled by peak current density. It was observed that SiO2 particles precipitated within grain interior by the transmission electron microscopy (TEM). Hardness and tensile strength of nanocomposites with a grain size larger than 35 nm was higher than that of nanocrystalline pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…10. The Hall-Petch relations in pure electrodeposited nanocrystalline Ni reported by the present authors [21] and El-Sherik [31] are also shown for comparison. According to our data, the hardness of pure nanocrystalline Ni and Ni-WO 3 with an average grain size of 45 nm is approximately 450 and 550 HV, respectively.…”
Section: Effect Of Dispersions On Hardness Of Nanocrystalline Nimentioning
confidence: 76%
See 1 more Smart Citation
“…10. The Hall-Petch relations in pure electrodeposited nanocrystalline Ni reported by the present authors [21] and El-Sherik [31] are also shown for comparison. According to our data, the hardness of pure nanocrystalline Ni and Ni-WO 3 with an average grain size of 45 nm is approximately 450 and 550 HV, respectively.…”
Section: Effect Of Dispersions On Hardness Of Nanocrystalline Nimentioning
confidence: 76%
“…Another method of synthesizing bulk nanocrystalline metals is electrodeposition, which is, from a synthesis point of view, one of the oldest methods used to produce nanostructured materials [16,17]. Nanocrystalline metals dispersed with hard particles have generally been plated using an electrolyte with suspended hard particles such as SiC [18], Al 2 O 3 [19], TiO 2 [20], and SiO 2 [21]. Similarly, particle size has been limited to dimensions larger than several microns to avoid agglomeration of particles during synthesizing.…”
Section: Introductionmentioning
confidence: 99%
“…Nano SiO 2 has unique physical and chemical characteristics due to its small size, large specific surface area, rich active hydroxy group, diversified hydroxyl structure, high reactivity, and strong adsorption power. Miyamoto et al [210] studied the mechanical properties of electrodeposited Ni-SiO 2 nanocomposite. They observed that it was at a grain size of 35 or 40 nm that the hardness of the Ni-SiO 2 nanocomposite was higher than that of nanocrystalline Ni.…”
Section: Formation Mechanism Of Nanocomposite Electroformingmentioning
confidence: 99%
“…With regard to the deformation mechanism of bulk nanocrystalline metals which have been discussed extensively, additional strengthening by fine dispersions in nanocrystalline metals are of increasing interest. 13) For example, additive strengthening by Orowan-type dislocationparticle interaction and the HallPetch effect in nanocrystalline materials has been discussed. 1) In addition to their strengthening, such very fine particles can stabilize the nanocrystalline structure whose low thermal stability is a drawback of nanocrystalline materials and has limited their industrial application in spite of very high interest in the scientific community.…”
Section: Introductionmentioning
confidence: 99%